Assessment of resisted trunk rotation exercise with and without Kiai double-pulse breathing technique on hockey shot velocity: A pilot study - Dagher, G.; Papuga, M. O. (Journal of Chiropractic Medicine, 2018)
Objective: The purpose of this study was to assess the feasibility of a study to measure the effect of resisted band antirotation exercises with the use of a double-pulse (DP) breathing kiai exercise on slapshot and snap shot velocity and subjective assessment of performance. Methods: Ten participants between 20 and 30 years of age who play ice hockey were recruited. The study was conducted over 3 weeks, and participants were randomized into 2 groups; group 1: resisted band antirotations with DP kiai (a shout used in martial arts) exercises, and group 2: resisted band antirotations alone. After week 1, there was a 1-week washout period, after which group 1 performed resisted band antirotations alone, and group 2 performed resisted band antirotations with DP kiai exercises. Results: Data were successfully collected on all 10 participants. There appeared to be no difference between groups regarding slapshot and snap shot velocity. Conclusion: The design for this study appears to be feasible. Preliminary data show that the average shot velocity before and after the intervention did not show a positive relationship between DP kiai breathing and hockey shot (slapshot and snap shot) velocity.